Practice of sustainable fashion design considering customer emotions and personal tastes - Kam, Seonju; Yoo, Youngsun (Frontiers in Psychology, 2022)
This study aimed to determine a sustainable design practice approach that can satisfy customer emotions and personal tastes, which designers need in the early stages of the SFD process, and improve environmental performance. The research was conducted through a case study and interviews. For case studies, the specific design methods of fashion brands, which have been ranked sustainable over the last 3 years in the world’s top fashion magazines favored by the public, were researched. The results of the case studies were used to draw questions for the in-depth interviews. The results are as follows: first, the design approaches of SFBs were categorized into “eco-friendly materials,” “functional durability design,” “reuse and remanufacturing,” “emotional durability design,” and sustainable fashion technology. Each type’s specific design approach methods were organized into a checklist for the practice of SFD and then reflected in the interview questions. From the results of the interviews, it was noted that the sustainable design approaches perceived by Korean designers were “eco-friendly materials,” “reuse and remanufacturing,” and “functional durability design.” Moreover, it was mentioned that specific methods of emotional durability design and sustainable fashion technology need to be acquired. By applying the checklist to the interviewees, interview participants could conveniently and quickly recognize how to apply sustainable design through the inventory. This study is significant because it presents a checklist, an efficient tool for sustainable design approaches, and a sustainable design practice method that can satisfy customer emotions and personal tastes and improve environmental performance.